2020
DOI: 10.1590/es.234058
|View full text |Cite
|
Sign up to set email alerts
|

“Nascer Em Berço De Ouro”: O Quarto Infantil Como Instância Socializatória

Abstract: RESUMO Este artigo apresenta parte de uma pesquisa realizada em quartos infantis de domicílios socioeconomicamente favorecidos. Diante da crescente importância desse cômodo, fenômeno que vem sendo chamado “cultura do quarto”, a pesquisa analisou a materialidade e os sentidos conferidos por pais e crianças a esse espaço. Os procedimentos de investigação consistiram em entrevistas com os pais e produção de vídeos nos quais crianças entre 3 e 11 anos apresentavam seus quartos. Como resultado, foram encont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
1
0
1
Order By: Relevance
“…2. For example, a recent study by Carvalho and Nogueira (2020), developed in the field of sociology of education, with children aged 3 to 11 years, identified that, among families with more significant cultural capital, children had a greater organization of room space, in compliance with the demands of the school culture. However, the study does not attempt to relate such practices to children's development.…”
Section: Final Considerationsmentioning
confidence: 99%
“…2. For example, a recent study by Carvalho and Nogueira (2020), developed in the field of sociology of education, with children aged 3 to 11 years, identified that, among families with more significant cultural capital, children had a greater organization of room space, in compliance with the demands of the school culture. However, the study does not attempt to relate such practices to children's development.…”
Section: Final Considerationsmentioning
confidence: 99%
“…Na interface entre os estudos sobre a cultura material da infância e aqueles sobre a socialização -uma agenda de pesquisa ainda pouco explorada, não só no Brasil (SETTON; BOZZETTO, 2020) como também em outros países, como a França (GARNIER, 2012) -, este trabalho é especialmente dedicado à análise do mercado de decoração infantil, apresentando parte de uma pesquisa de Doutorado sobre os quartos de crianças socioeconomicamente favorecidas (CARVALHO, 2018). Nele, esses cômodos são tomados como objeto empírico, constituindo uma janela para se descortinar o objeto teórico, a saber: a socialização das crianças desse grupo social.…”
Section: Introdução: a Socialização Infantil E A Cultura Materialsunclassified